Simulação acoplada CFD-DEM de reatores nucleares de leito fluidizado - Almeida, Lucilla Coelho de (2018)
Amongst the advantages of fluidized bed nuclear reactors, the improved heat transfer and mixing, the adjustment of the refrigerant flow rate as an extra control mechanism and the possibility of removing the fuel by gravity from the movable core in the event of an accident stand out. Accurate modelling of the particles and the refrigerant behavior is required to reliably evaluate the thermo-hydraulic efficiency and margin of safety of these reactors. This work presents a CFD-DEM coupling approach using an improved heat conduction formulation for spherical particles. In this approach, particles are treated as a discrete phase following the DEM approach, while the fluid is treated as a continuous phase, described by the volume averaged Navier-Stokes equations. Instead of approximating the surface temperature by the average temperature of the particle through classical lumped approach, an improved lumped model was developed, relating the surface to particle average temperatures and surface heat flux by Hermite-type approximations for integrals. Simple cases were used to validate the proposed coupling methodology and their results compared against analytical or empirical results. Then, the proposed method was applied to the simulation of a Geldart D bubbling fluidized bed. The numerical results obtained using the classical and improved formulations are compared with experimental pressure and velocity data, showing good agreement. The temperature results show that the uniform particle temperature assumption can influence the heat transfer calculation, predicting smaller bed temperatures than obtained in reality.